The Impact of Waqf from a Macroeconomic Perspective as An Instrument of State Revenue - Nasriandani, Elvi (Pascasarjana Universitas Pasundan, 2023)
The purpose of this study is to explore the impact of waqf from a macroeconomic perspective as a tool for state revenue. The research delves into the role of waqf in the economy from a macroeconomic standpoint, considering its historical significance during the heyday of Islam, its management in various Muslim countries, and its development within Indonesia. Employing a qualitative descriptive methodology, the study gathers data through literature review, incorporating sources such as the Central Bureau of Statistics, books, national and international journals, Al-Qur'an, and Hadith. The research is essentially a descriptive analysis, which involves periodic collection and analysis of data and literature. The focus is on cash waqf, which manifests as sukuk, mutual funds, and similar forms. The findings indicate that waqf can play a pivotal role in a country's development by fostering new public institutions that bolster the State Budget (APBN). Waqf funds can address key developmental challenges such as poverty, unemployment, and healthcare issues. The impact of waqf is evident across Muslim nations, with its management traced through history, legal frameworks, and asset administration. An example is the management of Al-Azhar University. In Indonesia, waqf's impact is multi-faceted. It generates employment opportunities through endeavors like rice seed breeding, cattle breeding support, and support for micro, small, and medium enterprises (MSMEs). Additionally, it enhances education by offering scholarships at all levels, supporting educators, and implementing educational initiatives. The health sector benefits from medical equipment aid, ambulance services, and financial assistance for underprivileged patients. Furthermore, waqf contributes to the construction of mosques and other community-focused projects. This study underscores the potential of waqf to shape and drive societal development through its multifaceted impacts on various sectors in both Muslim countries and Indonesia.